A Literature Study on Conflict and Compromise in Islamic Education Policy in Indonesia - Nurul Qomariyah; Muhammad Qomari Romadhon; Muhammad Sirozi (Didaktika: Jurnal Kependidikan, 2025)
Islamic education in Indonesia continues to evolve amidst social, political and economic dynamics. This study aims to analyze conflicts and compromises in contemporary Islamic education politics in Indonesia using the literature study method. The results show three main forms of conflict: differences in views between Islamic organizations, imbalance between religious and general education, and state intervention in the curriculum. On the other hand, compromise is reflected in the policies of integrating Islamic education into the national curriculum, developing modern pesantren, and autonomy in the management of Islamic education institutions. These findings provide an overview of the political dynamics of Islamic education and the importance of strengthening an education system that is inclusive and adaptive to changing times.